FAKTOR-FAKTOR YANG MEMPENGARUHI UPAH MINIMUM REGIONAL DI PROVINSI JAWA TENGAH - Desty Richqi Ramdhansya; Lucia Rita Indrawati (LP2M Universitas Bina Bangsa, 2022)
Minimum wage is the minimum standard in the form of money used by employers to pay workers' salaries after doing their work. A minimum wage is a form of effort to improve people's standard of living with less or low incomes. The goal is to earn wages to meet the needs to improve a person's standard of living. The level of wages of workers needs to be improved so that the quality of life of workers and their families can also increase. Wages can be given based on the amount of time spent working and units of goods that workers can afford to distribute. Thus, if the minimum wage level given is higher, then the higher the community's income so that the level of welfare also increases. This study aims to determine the effect of economic growth, inflation, and living needs on the regional minimum wage of 6 cities in Central Java Province. Using Central Java BPS data and regression panel data with REM approach. The result is (1) Economic Growth has no significant effect on the Regional Minimum Wage in 6 Cities of Central Java Province in 2010-2019, (2) Inflation has no significant effect on the Regional Minimum Wage in 6 Cities of Central Java Province in 2010-2019, (3) Living Needs positively and significantly on the Regional Minimum Wage in 6 Cities of Central Java Province in 2010-2019, (4) Economic Growth, Inflation, and Living Needs together have a significant effect on the Regional Minimum Wage in 6 Cities of Central Java Province 2010-2019